[IN1438] Dengue and Dengue Virus in Florida - Yasmin V. Ortiz; Daniel W. Pérez-Ramos; Eric P. Caragata; Panpim Thongsripong (EDIS)
This publication provides an overview of dengue fever, focusing on its epidemiological landscape in Florida. Dengue, caused by dengue virus and transmitted through the bites of infected Aedes mosquitoes, is a major global health concern. Florida has experienced local dengue transmissions, and the incidence of dengue is increasing in the state. The biology and ecology of the primary vectors, Aedes aegypti and Aedes albopictus, play  important roles in the disease's transmission cycle. No vaccine and no specific antiviral treatments are yet available, and diagnosis is difficult because dengue symptoms overlap with those of other, similar febrile illnesses. Prevention and control strategies, such as mosquito management, are therefore crucial to mitigate disease risks. Alongside urbanization, climate change, and globalization, incidence of dengue is increasing in Florida. Continued vigilance and research will help to combat this public health threat.